(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The purpose of the paper is to pinpoint the distinctive traits of translation transformation strategies applied to the translation of fiction, using the modernist novel "Ulysses" by Irish author James Joyce as an illustration. The study employed a descriptive qualitative design, a type of inquiry that clarifies the process’s description by comparing translations with their original sources. Additionally, these strategies or methodologies might highlight parallels and discrepancies between the source language and the target language. The information was collected from "Ulysses" Vol. 1 in Russian translation from 2000 and Vol. 1 in Uzbek translation from 2008, respectively. The results demonstrate the existence of four translational strategies: transposition, replacement, adjunction, and deletion, along with examples of each. While doing study, we made an effort to compare statements with the syntactic changes that were made from the original language (SL) into the translating language (TL). In actuality, these methods are frequently employed due to the distinct grammar between SL and TL, where academics also present their theoretical perspectives on transformation.